Consumption of Ultraprocessed Foods by Pregnant Women with Diabetes Mellitus (P11-021-19). (13th June 2019) - Padilha, Patricia; Felizardo, Carolina; Saunders, Claudia; Cunha, Letícia; Pinheiro, Amanda; Belfort, Gabriela; Santos, Karina; Ferreira, Nathália
Abstract: Objectives: To evaluate the consumption of ultraprocessed foods (UPF)by pregnant women with previous diabetes mellitus (DM) in use of the method of counting carbohydrates, besides investigating their association with the outcomes of total gestational weight gain and glycemic control. Methods: A cohort study developed in a reference maternity hospital in the city of Rio de Janeiro, Brazil, with adult pregnant women with single fetus, with a diagnosis of DM prior to pregnancy, without other chronic morbidities. Food consumption was assessed by the semi-quantitative frequency of consumption questionnaire in the second and third quarters and the NOVA classification was used to identify the consumed of UPF. Measurements of weight were measured at all consultations and laboratory tests were evaluated at each gestational trimester. The multivariate linear regression was used in the analysis. Results: Pregnant women (n = 42) presented mean total gestational gain of 12.02 ± 4.8 kg, 65.8% of them with inadequacy. The daily consumption of UPF was 317.29 ± 187.28 Kcal and 272.37 ± 170.55 Kcal, respectively, representing 16.9 ± 7.7% and 15.2 ± 10% of the average daily energy consumption. The increase of every 1 kcal in the caloric intake from UPF in the third trimester increased the glycated hemoglobin in the third trimester (β = 0.007, P  = 0.025), 0.14mg/dL of postprandial 1-hour glycemia in the third trimester (β = 0.143, P  = 0.011) and 0.11 kg in the total gestational weight gain (β = 0.11, P  = 0.006). No associations were found for ultraprocessed foods consumption in the second trimester. Conclusions: Ultraprocessed foods consumption was associated with the gestational endpoints glycemic control and total weight gain. It is necessary to intensify the strategies of orientation and nutritional education for pregnant women with previous DM in use of the method of counting carbohydrates. Funding Sources: FAPERJ.